PEMBUATAN GAME RHYTHM VR “SABEAT” PADA ANDROID - Yobel Octavinus; Jeanny Pragantha; Darius Andana Haris (Fakultas Teknologi Informasi Universitas Tarumanagara, 2020)
The game is developed by Unity Game engine and Monodevelop as a script maker in C# language. The game consist of 10 Electro musics. A blue or red flashlight is used to control the game. The player use the flashlight as a saber to cut the cube. To win the game the player has to cut the cube more than 70% of cube. Testing is done by blackbox testing, alpha testing by the supervisor, and beta testing by using survey of 31 respondents. The test results show that the game